(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Ayurveda is the most popular ancient system of medicine. It is based on principle of prevention is better than cure. Vata, Pitta, Kapha-collectively known as the doshas, are one of the fundamental concepts in the tradition of Ayurveda. When balanced, the doshas maintain the system of body, but when one of the dosha increases due to certain diet and lifestyle habits, imbalance is created and causes a number of disorders which have become a challenge for human. Among these Raktagata Vata is considered to be most serious disorder and frustrating ailment for the patient. Raktagata Vata is one of the most important diseases explained in classics affecting Rakta- dhatu. According to Ayurveda Raktagata Vata is due to vitiation of Vata by Swanidana. Vaidya Y.N. Updahyaya had equated the term Raktagata Vata for hypertension. Now-a-days hypertension is the most common life style disorder. It is due to changing life style such as excessive intake of spicy, salty food, and insufficient consumption of fruits and vegetables, stress factor and faulty life style, lack of exercise also responsible for hypertension. Hypertension is an important worldwide public health challenge and remains a major cause of morbidity and mortality worldwide. About 26.4% of the world adult population in 2000 had hypertension and 29.2% were projected to have this condition by 2025. An Nidanatmaka (epidemiological) Study on Raktagata Vata (Hypertension) and A Upashyatmaka(Therapeutic) Study to Evaluate the Efficacy of Aswagandha Churna to evaluate the aetiopathological aspect of the disease Raktgata Vata (Hypertension).